Biomimetic Macrocyclic Inhibitors of Human Cathepsin D: Structure-Activity Relationship and Binding Mode Analysis - Houštecká, Radka; Hadzima, Martin; Fanfrlík, Jindřich; Brynda, Jiří; Pallová, Lenka; Hánová, Iva; Mertlíková-Kaiserová, Helena; Lepšík, Martin; Horn, Martin; Smrčina, Martin; Majer, Pavel; Mareš, Michael (Journal of medicinal chemistry, 2020)
Human cathepsin D (CatD), a pepsin-family aspartic protease, plays an important role in tumor progression and metastasis. Here, we report the development of biomimetic inhibitors of CatD as novel tools for regulation of this therapeutic target. We designed a macrocyclic scaffold to mimic the spatial conformation of the minimal pseudo-dipeptide binding motif of pepstatin A, a microbial oligopeptide inhibitor, in the CatD active site. A library of more than 30 macrocyclic peptidomimetic inhibitors was employed for scaffold optimization, mapping of subsite interactions, and profiling of inhibitor selectivity. Furthermore, we solved high-resolution crystal structures of three macrocyclic inhibitors with low nanomolar or subnanomolar potency in complex with CatD and determined their binding mode using quantum chemical calculations. The study provides a new structural template and functional profile that can be exploited for design of potential chemotherapeutics that specifically inhibit CatD and related aspartic proteases.
Keywords: Protein Binding; vazebná místa; pepstatiny; Enzyme Assays; Protease Inhibitors; kathepsin D; Structure-Activity Relationship; molekulární struktura; Molecular Structure; inhibitory proteas; Cathepsin D; biomimetické materiály; vztahy mezi strukturou a aktivitou; vazba proteinů; Binding Sites; kinetika; lidé; Peptides, Cyclic; Humans; Caco-2 Cells; Caco-2 buňky; Biomimetic Materials; enzymatické testy; cyklické peptidy; Kinetics; Pepstatins